La comunicación oral en inglés en estudiantes del sexto ciclo de educación básica regular en la institución educativa parroquial Virgen de Loreto en cuanto al sexo, Iquitos 2020 - Restuccia Díaz, Duilia Giovanna (2021)
The objective of this study was to compare Regular Basic Education sixth cycle students’ achievement in listening and speaking skills in English at Virgen de Loreto Parish School in terms of sex, Iquitos 2020. The type of research was comparative with field study, contemporary transectional and univariable designs. The population was made up by 360 students and a deterministic sample of 160, 88 female and 72 male students, distributed in 9 classes. Data gathering tools were valid and reliable oral comprehension test, speaking performance test, and rubrics. Results show that both female and male students are at a beginner level in oral communication since the main scores were 7,838 for female students and 7,862 for male students. The same happens in its dimensions: Getting information (10.753 and 10.625), inferencing and interpreting information (10.429 and 10.710), strategic interaction (5,697 and 5.722 pre-beginner), use of non-verbal and paraverbal resources (5,163 and 5,174 pre-beginner). The U test of Mann-Whitney for independent samples showed that there is no statistically significant difference in the achievement of oral communication in male and female students in the study population as p-value = 0.165 > ? = 0.05, rejecting the working hypothesis.